FORMULASI LOTION EKSTRAK DAUN Meistera chinensis SEBAGAI TABIR SURYA Meistera chinensis LEAF EXTRACT LOTION FORMULATION AS SUNSCREEN - Nirwati rusli; yulianti fauziah; Elviyanti Yusdin (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Excessive sunlight can have a negative impact on skin health, but the bad effects of sunlight can be overcome by using sunscreen preparations. One of the natural ingredients that can be used in the manufacture of lotion sunscreenisleaf Meistera chinensis. Meistera chinensis is a plant that belongs to the Zingiberaceae family. Previous research has stated that Zingiberaceae species such as Etlingera elatior (torch ginger) have one of the functions as antioxidants. This study aims to formulateleaves Meistera chinensis as sunscreen and determine the SPF value obtained. Leaf extract was Meistera chinensis extracted using maceration method using methanol as solvent. Physical evaluation tests, stability tests, and sunscreen activity were carried out at three concentrations, namely 1% (F1), 3% (F2) and 5% (F3) concentrations. The three formulations are pale green, green, and dark green in color, have a melon flavor and have a liquid and semi-solid texture, are homogeneous with an oil-in-water (W/A) emulsion type and meet the pH requirements of 6 and 7. The stability test results show that the three formulas do not stable because it is not homogeneous and there is a change in aroma after the cycling test. The SPF value increased along with the increase in extract concentration, namely 7.46 (extra protection), 14.12 (maximum protection), and 19.06 (ultra protection). Keywords: Extract, Leaf Meistera chinensis, Lotion, Sunscreen, SPF